Galacto-oligosaccharides production during lactose hydrolysis by free Aspergillus oryzae β-galactosidase and immobilized on magnetic polysiloxane-polyvinyl alcohol - Neri, D. F. M. (2009)
The synthesis of galacto-oligosaccharides (GOS) by the action of Aspergillus oryzae β-galactosidase free and immobilized on magnetic polysiloxane-polyvinyl alcohol (mPOS-PVA) was studied. A maximum GOS concentration of 26% (w/v) of total sugars was achieved at near 55% lactose conversion from 50%, w/v lactose solution at pH 4.5 and 40 °C. Trisaccharides accounted for more than 81% of the total GOS produced. GOS formation was not considerably affected by pH and temperature. The concentrations of glucose and galactose encountered near maximum GOS concentration greatly inhibited the reactions and reduced GOS yield. GOS formation was not affected by enzyme immobilization in the mPOS-PVA matrix, indicating the absence of diffusional limitations in the enzyme carrier. Furthermore, this water insoluble magnetic derivative was reutilized 10-times and retained about 84% of the initial activity. In addition, the kinetic parameters for various initial lactose concentrations were determined and compared for the free and immobilized enzyme.